Doses de glyphosato sobre as características agronômicas e fisiológicas da soja RR em condições de várzea sistematizada - Ribeiro, Francisco de Carvalho (Universidade Federal do Tocantins, 2017)
Problems caused by glyphosate herbicide in RR soybean crop are a very current issue. However, much of the currently available studies reveal the possible negative effects of glyphosate on the growth and development of RR soybeans. With the continual increase of the RR soybean area in the world, many farmers report that some varieties show signs of injury after application, and are grown in areas with difficult to control weeds. The objective of this work was to evaluate the effects of increasing doses of glyphosate herbicide on agronomic traits and photosynthetic parameters of RR soybean under conditions of lowland systematized. The following agronomic characters were evaluated: Weed densities at 0 DAA and 21 DAA, Control of weeds at 7, 14, 21 DAA, Phytotoxicity at 7,14 and 21 DAA, dry mass of plant-1 part, dry mass of palnta-1 root, height of Plants, first pod insertion, plant-1 pod numbers, 1,000 grain mass and grain yield. For the physiological parameters photosynthesis, stomatal conductance, internal carbon, transpiration, water use efficiency and intrinsic efficiency were evaluated in lowland conditions.